Analysis of the Effect of Body Lossion of Rattus Norvegicus on Granulation Formulation of Chitosan Waste Shell of Placuna Placenta - Ariyanti Ariyanti; Eni Masruriati; Ade Novitasari; Suzana Wulandari (Indonesian Journal of Global Health Research, 2020)
Weight loss Rattus norvegicus wistar strain can be done by a variety of chemical and traditional medicine. One of the traditional medicines used for weight loss is to use Placuna Placenta chitosan. The purpose of this study was to determine the optimal concentration of Placuna Placuna Placenta granules as a weight loss agent for Rattus norvegicus. This study was an experimental study with 5 concentrations of 5%, 7.5% and 10% Placuna Placuna Placenta chitosan observed for 30 days. The positive control used weight loss drugs in the market, while the negative control used granule formulation without the addition of Placuna Placuna Placenta chitosan. The experimental research design posttest only control group design, treatment or intervention in the experimental group by comparing groups. Comparisons or differences were analyzed statistical tests using the ANOVA test. The optimal concentration of chitosan granule formulation of Placuna Placuna Placenta as a weight loss for Rattus norvegicus wistar strain was 10%.